2017
DOI: 10.3389/fpsyt.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Consolidation, Reinstatement, and Renewal of Conditioned Fear Memory by Repetitive Treatment of Radix Polygalae in Mice

Abstract: The therapeutic goal for the treatment of posttraumatic stress disorder (PTSD) is to promote extinction and to prevent the relapse of fearful memories. Research has identified pharmacological treatments that may regulate the formation and extinction of fear memories, but not many reagents that block the relapse of extinguished fear are known. Radix Polygalae (RP) is an Asian herb used for sedation, and its ingredients have anxiolytic and antidepressant properties. As various neurological effects have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In both Aβ-induced PC12 cells and AD rats, LSS can reduce the expression of homocysteine-3 and Bax, while increasing the expression of Bcl-2 and the ratio of Bcl-2/Bax, reversing apoptosis, and, ultimately, alleviating cognitive dysfunction in AD rats [ 234 ]. Polygalasaponin F (PGSF), a triterpenoid saponin monomer isolated from P. japonica, has been shown to improve hippocampal-dependent learning memory capacity [ 235 ]. Furthermore, it has also been reported to reduce the number of caspase3-positive cells, thereby reversing glutamate-induced apoptosis in primary hippocampal neurons [ 236 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%
“…In both Aβ-induced PC12 cells and AD rats, LSS can reduce the expression of homocysteine-3 and Bax, while increasing the expression of Bcl-2 and the ratio of Bcl-2/Bax, reversing apoptosis, and, ultimately, alleviating cognitive dysfunction in AD rats [ 234 ]. Polygalasaponin F (PGSF), a triterpenoid saponin monomer isolated from P. japonica, has been shown to improve hippocampal-dependent learning memory capacity [ 235 ]. Furthermore, it has also been reported to reduce the number of caspase3-positive cells, thereby reversing glutamate-induced apoptosis in primary hippocampal neurons [ 236 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%
“…Polygalae Radix extract is used in Japanese medicine to treat memory loss in patients with AD [16] . In Korean medical research, Polygalae Radix was shown to effectively inhibit memory consolidation of post‐traumatic stress disorder for primary and secondary prevention [17] . Codonopsis polysaccharide in Codonopsis improved MI in mice by increasing the level of acetylcholine, clearing free radicals, and upregulating the expression of α7‐nAChR and CaMKII protein [18] .…”
Section: Introductionmentioning
confidence: 99%
“…[16] In Korean medical research, Polygalae Radix was shown to effectively inhibit memory consolidation of post-traumatic stress disorder for primary and secondary prevention. [17] Codonopsis polysaccharide in Codonopsis improved MI in mice by increasing the level of acetylcholine, clearing free radicals, and upregulating the expression of α7-nAChR and CaMKII protein. [18] In the early stage of our research, we used D-galactose combined with aluminum chloride to establish a rat model of MI.…”
Section: Introductionmentioning
confidence: 99%
“…or Polygala sibirica L 1 . Modern pharmacological studies indicate that Radix Polygalae possesses various biological activities against certain ailments, such as cerebrovascular diseases, senile dementia and depression 24 . Moreover, some researchers found that Radix Polygalae could effectively suppress the consolidation and reinstatement of fear memories 5 .…”
Section: Introductionmentioning
confidence: 99%